Harmonized NDVI time-series from Landsat and Sentinel-2 reveal phenological patterns of diverse, small-scale cropping systems in East Africa - Adomas Liepa; Michael Thiel; Hannes Taubenböck; Ingolf Steffan-Dewenter; Itohan-Osa Abu; Maninder Singh Dhillon; Insa Otte; Michael Hilary Otim; Moses Lutaakome; David Meinhof; Emily A. Martin; Tobias Ullmann (Remote Sensing Applications: Society and Environment, 2024)

Atmospheric moisture pathways of East Africa and implications for water recycling at Mount Kilimanjaro - Benjamin Schumacher; Marwan Katurji; Hanna Meyer; Tim Appelhans; Insa Otte; Thomas Nauss (International Journal of Climatology, 2020)
The Mt. Kilimanjaro ecosystem depends on atmospheric moisture transport and recycling of water, yet limited knowledge on the relation between advective moisture pathways and local water recycling is available. This study uses a regional atmospheric model to analyse moisture source and sink processes as well as precipitation recycling at Mt. Kilimanjaro. The results indicate that locally produced precipitation is deposited mainly in June and July while trans‐regional effects are weak. Results also revealed the importance of tropical storm systems for local convection in the Kilimanjaro region and the effect of the Indian Ocean Zonal Mode phases on East African moisture pathways. The analysis further revealed connections between the Madagascar tip jet and the Turkana jet with implications for regional moisture pathways that have not been described before.

Spatial and temporal 2 H and 18 O isotope variation of contemporary precipitation in the Bale Mountains, Ethiopia - Bruk Lemma; Seifu Kebede Gurmessa; Sileshi Nemomissa; Insa Otte; Bruno Glaser; Michael Zech (Isotopes in Environmental and Health Studies, 2020)

A glimpse at short-term controls of evapotranspiration along the southern slopes of Kilimanjaro - Florian Detsch; Insa Otte; Tim Appelhans; Thomas Nauss (Environmental Monitoring and Assessment, 2017)

Eco‐meteorological characteristics of the southern slopes of Kilimanjaro, Tanzania - Tim Appelhans; Ephraim Mwangomo; Insa Otte; Florian Detsch; Thomas Nauss; Andreas Hemp (International Journal of Climatology, 2016)
This study introduces the set‐up of a new meteorological station network on the southern slopes of Kilimanjaro, Tanzania, since 2010 and presents the recorded characteristics of air temperature, air humidity and precipitation in both a plot‐based and area‐wide perspectives. The station set‐up follows a hierarchical approach covering an elevational as well as a land‐use disturbance gradient. It consists of 52 basic stations measuring ambient air temperature and above‐ground air humidity and 11 precipitation measurement sites, with recording intervals of 5 min. With respect to precipitation observations, the network extends the long‐term recordings of A. Hemp who has installed and maintained up to 117 multi‐month accumulating rainfall buckets in the region since 1997. The meteorological characteristics of the study region based on the derived data since 2010 are mostly in line with previous studies, although we see increased precipitation amounts at higher elevations during these years when compared with long‐term means. We furthermore identify a mean annual condensation level at about 2300 m a.s.l. which has not been reported before. Finally, this is the first study to provide high resolution maps of mean monthly and mean annual temperature, humidity and precipitation for Kilimanjaro, which are of great value for geographically oriented meteorological or ecological investigations. Detailed performance statistics of the geo‐statistical and machine learning techniques used for the gap filling of the recorded meteorological time series and their regionalization to the Kilimanjaro region indicate that the presented data sets provide reliable measurements of the meteorological reality at Kilimanjaro.